2012
DOI: 10.5539/jas.v4n5p139
|View full text |Cite
|
Sign up to set email alerts
|

Repellent Effect of Herb Extracts on the Population of Wingless Green Peach Aphid, Myzus persicae Sulzer (Hemiptera: Aphididae)

Abstract: Investigation of the repellent and insecticidal effects of 8 kinds of herb extracts (chives, dokudami, eucalyptus, lavender, peppermint, cherry sage, sweet pepper and tansy) against wingless green peach aphids were conducted in laboratory and field test.In laboratory repellent tests, 20 aphids were placed between a radish leaf and filter paper for 16 h and aphids on radish leaf were calculated. In laboratory insecticide tests, 20 aphids were placed on a radish leaf treated with herb extract, and live aphids we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 14 publications
(17 reference statements)
2
19
1
1
Order By: Relevance
“…Nana only acted on their olfactory orientation in the presence of or via the host plant ( C. annuum ). Contrary to other studies, our findings demonstrated that none of the headspace volatiles from L. latifolia , M. piperita or R. officinalis plants exhibited significant negative effects against M. persicae . Differences between results were probably related to qualitative (presence/absence of specific VOCs) and quantitative variations among the chemical composition of volatiles perceived by aphids .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Nana only acted on their olfactory orientation in the presence of or via the host plant ( C. annuum ). Contrary to other studies, our findings demonstrated that none of the headspace volatiles from L. latifolia , M. piperita or R. officinalis plants exhibited significant negative effects against M. persicae . Differences between results were probably related to qualitative (presence/absence of specific VOCs) and quantitative variations among the chemical composition of volatiles perceived by aphids .…”
Section: Discussioncontrasting
confidence: 99%
“…VOCs from rosemary ( Rosmarinus officinalis L.) plants are effective as a good aphid repellent . Similar properties have been reported for volatiles from lavender ( Lavandula latifolia L.) and peppermint ( Mentha piperita L.) …”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…The studies so far indicate the effectiveness of peppermint extracts in certain aphid species combating, e.g. peach-potato aphid (Myzus persicae Sulzer) [Ikeura et al 2012]. In turn, the essential oils of peppermint were tested for toxicity against mosquitoes, as reported by Ansari et al [2000] and Kumar et al [2012].…”
Section: Effect Of Water Extract From Mint On Selected Crop Pests Feementioning
confidence: 99%